To Achieve Software Quality Assurance in Brain Tumor Detection Using Artificial Neural Networks - Praba, V; Sivakumar, S (International Journal of Computer Sciences and Engineering, 2025)
Quality assurance is a way of preventing errors and avoiding problems when distributing software to clients. The term quality assurance is refers to ways of ensuring the quality of a product. Here we detect the brain tumor detection with segmentation using genetic algorithm and testing that application output by ANN. Brain is the central nervous system of a human being one of the major causes of death among people is brain tumor. In medical field like this kind of causes are struggling to detect automatically with quality. Here provided solution to detect the tumor automatically the same way testing the automated output by ANN for improving the quality of software. Proposed method integrates image pre-processing, future extraction, segmentation, classification and testing.